Teaching mands for information using 'when' to children with autism. Issue 3 (28th April 2017) - Landa, Robin K.; Hansen, Bethany; Alice Shillingsburg, M.
Abstract : Previous research has evaluated contrived motivating operations to teach mands for information. However, literature evaluating acquisition of the mand when? is comparatively limited. As an extension of Shillingsburg, Bowen, Valentino, & Pierce (2014), we taught three children with autism to engage in mands for information using when under alternating conditions in which a contrived establishing operation was present (EOP) or absent (EOA). Following training with a constant prompt delay, all participants acquired the mand for information and demonstrated correct use of the provided information and a decrease in inappropriate attempts to access restricted items.